Improving Hydrophobicity and Oil Barrier Performance of Paper by Coating with PVA/Nanocellulose-Based Suspension - Tanjung, Faisal Amri; Arifin, Yalun; Gunawan, Chandra; Fung, Liem Khe (Jurnal Teknologi Lingkungan, 2024)
This study investigates the use of nanocellulose and polyvinyl alcohol (PVA) suspension as a coating formulation on a paper substrate and its effects on the paper’s oil and water barrier properties. The PVA/nanocellulose coating suspension was prepared via a simple nanocellulose mixing procedure with various concentrations of PVA. The coating was carried out by depositing an adhesive agent and multiple layers of nanocellulose/PVA suspension on the paper surface using a bar coater. The results showed that coating up to the fourth layer decreased the opacity index and air permeability rate of the coated papers, but there was a slight increase in the air permeability at the sixth layer. The deposition of PVA/nanocellulose suspension on the paper surface also increased the water and oil barrier performance. The highest contact angle (CA) of 82° and oil kit value of 14 was obtained at the fourth layer of coating using suspension with 2 wt% of PVA content, as compared to the uncoated paper (CA 43°). It is interesting to note that coating paper using nanocellulose/PVA suspension can effectively enhance the hydrophobicity and oil barrier performances of the paper. This satisfactory results in paper properties after being coated with nanocellulose/PVA suspension can be a potential environmentally friendly material in food packaging applications.